Utilization Of Social Media As A Strategy For Business Actors In Dealing With The Covid-19 Pandemic (Journal of Private and Commercial Law, 2021)
Micro-enterprises, which run their businesses around campus, have been greatly affected by the COVID-19 pandemic. The decrease in income from micro business actors occurs because they are still using the traditional marketing model, namely marketing from one person to another. This condition requires changes from business actors, to change their business marketing model. Changes in business marketing models, it has become a must to take advantage of social media. Marketing activities using social media turned out to have a positive impact on increasing omzet sales for micro business actors around campus. Micro-enterprises can carry out their business continuity and maintain their business. Social media has become one of the means to change the behavior of business actors in facing the challenges of technological progress. Social media is also a solution to face government policies by implementing social distancing. The purpose of this article is to describe the problems faced by micro-enterprises around campus in Semarang City, Central Java Province, which are experiencing the impact of the COVID-19 pandemic and provide solutions for using social media in marketing their products.